Functional Properties of Donor (Al) and Acceptor (Cu) Codoped High Dielectric Constant ZnO Nanoparticles. (13th January 2022) - Tariq, Huma; Azad, Fahad
Abstract : In this work, we have synthesized donor-acceptor (Al-Cu) codoped ZnO nanoparticles with a doping concentration of 0%, 0.25%, 0.5%, and 0.75% by coprecipitation method. The synthesized samples were then annealed at 350°C and 600°C. All the samples showed wurtzite structure of ZnO with no secondary phase. The increase in doping concentration led to deterioration of crystalline quality, while improved crystallinity was observed at higher annealing temperature. The morphological study of these samples showed good grain-to-grain contact with less isolated pores. These samples were further characterized by impedance spectroscopy for analyzing dielectric properties. The values of the real part of dielectric constant and tangent loss showed decreasing trend with frequency. The appearance of semicircular arcs in the impedance complex plane plots indicates contribution of grains and grain boundaries and presence of different relaxation processes. 0.5% Al and Cu codoped ZnO showed the best dielectric response with a high value of dielectric constant and low tangent loss.